2005
DOI: 10.1021/ie0401758
|View full text |Cite
|
Sign up to set email alerts
|

Study on the FCC Process in a Novel Riser−Downer−Coupling Reactor (II):  Simulation and Hot Experiments

Abstract: In this paper, a two-dimensional dispersion model is developed to simulate the FCC process occurring in the riser−downer−coupling reactor based on the hydrodynamics and mixing behaviors described in the previous paper as well as an 11-lump reaction kinetics model. The merits and defects of both riser and downer are discussed on the basis of the simulation results. It can also be concluded from the calculation that the coupling reactor can take advantage of both the riser and downer to offer the highest yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Studies on the downer reactor started in the 1990s and there is now a substantial amount of understanding of the flow behaviors in the downer . The downer has a distinct axial flow structure in the downer due to the concurrent gas‐solids flow in the direction of gravity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the downer reactor started in the 1990s and there is now a substantial amount of understanding of the flow behaviors in the downer . The downer has a distinct axial flow structure in the downer due to the concurrent gas‐solids flow in the direction of gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al reported the hydrodynamics and reactor performance using a hot model reaction (ozone decomposition) in a downer. Those studies were, however, carried and with low solids circulation rates, less than 200 kg/m 2 s, even though many industrial CFB reactors such as FCC (where solids flux normally ranges from 400 to 1200 kg/m 2 s) are operated at much higher solids circulation rate with higher solids holdup.…”
Section: Introductionmentioning
confidence: 99%
“…The test results in the industry indicated that the selectivity to desired products could be improved in the coupling reactor as a result of the introduction of the downer part. 12 When the downer was operated as the FCC reactor separately, the yields of gasoline, liquefied petroleum gas (LPG), and propylene were increased by 3.90, 8.14, and 4.30 wt %, respectively, in contrast to a conventional riser. Meanwhile, the diesel oil and dry gas were decreased by 10.48 and 1.83 wt %, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many researchers have simulated the fluidized reactions of fluid catalytic cracking, 18,19 ozone decomposition, 20−22 methanol to olefins, 23,24 carbon monoxide oxidation, 25 catalytic combustion of methane, 26 and other processes 6 using the multiscale-or cluster-based mass transfer model and obtained satisfying results, which confirms that it is rational to forecast the mass transfer behavior in consideration of the fluidized structural effect. However, compared with the above numerical studies that mainly focus on the catalytic gasphase reaction, the non-catalytic solid-phase process further involves the variation of the particle diameter and density, the alteration of gas/solid holdup, and the constitution of kinetics and the rate-controlling mechanism, all of which have not been analyzed comprehensively coupled with mass transfer simulation yet.…”
Section: Introductionmentioning
confidence: 80%